It's a wrap: encapsulation as a management tool for marine biofouling. Issue 3 (15th March 2016) - Atalah, Javier; Brook, Rosemary; Cahill, Patrick; M. Fletcher, Lauren; A. Hopkins, Grant
Abstract: Encapsulation of fouled structures is an effective tool for countering incursions by non-indigenous biofoulers. However, guidelines for the implementation of encapsulation treatments are yet to be established. This study evaluated the effects of temperature, biomass, community composition, treatment duration and the biocide acetic acid on biofoulers. In laboratory trials using the model organisms Ciona spp. and Mytilus galloprovincialis, increasing the temperature or biomass speeded up the development of a toxic environment. Total mortality for Ciona spp. occurred within 72 and 24 h at 10 and 19°C, respectively. M. galloprovincialis survived up to 18 days, with high biomass increasing mortality at 10°C only. In a field study, three-month-old and four-year-old communities were encapsulated with and without acetic acid. Mortality took up to 10 days for communities encapsulated without acetic acid, compared to 48 h with acetic acid. The insights gained from this study will be useful in developing standardised encapsulation protocols.